2009
DOI: 10.1080/00207590903165059
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment styles and cognitive vulnerability to depression in a sample of undergraduate students: The mediational roles of sociotropy and autonomy

Abstract: We analysed the mediational role of the personality dimensions of sociotropy and autonomy in the relationship between certain styles of attachment and depressive symptoms. In order for us to do so, a group of university students filled out the Beck Depression Inventory (BDI), the Revised Personal Style Inventory (PSI-II) and the Relationship Questionnaire (RQ). Individuals having attachment styles with a negative model of self (preoccupied and fearful) obtained significantly higher scores in the BDI than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…This result is coherent with the studies that showed an association between the anxious-preoccupied attachment style and depression levels. 50 This finding contributes to focusing clinical attention on this relational dimension in caregivers of terminally ill patients with cancer. Moreover, it suggests to consider psychological treatments focused on the relationship with the loved one and oriented to increase the acceptance of the imminent loss and to decrease denial and self-blame 13 in order to prevent the onset of prolonged grief.…”
Section: Discussionmentioning
confidence: 92%
“…This result is coherent with the studies that showed an association between the anxious-preoccupied attachment style and depression levels. 50 This finding contributes to focusing clinical attention on this relational dimension in caregivers of terminally ill patients with cancer. Moreover, it suggests to consider psychological treatments focused on the relationship with the loved one and oriented to increase the acceptance of the imminent loss and to decrease denial and self-blame 13 in order to prevent the onset of prolonged grief.…”
Section: Discussionmentioning
confidence: 92%
“…These people have mental health, are less aggressive and use rational ways of resolving their problems (5). In the dependent attachment style, people need an emotional relationship and act more rational than anxious people in the avoidance of loneliness (20). …”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was determined that as the preoccupied attachment style increased, the relational self-construal increased. In the preoccupied attachment style, the individual is in need of establishing close relationships with other individuals (Permuy, Merino, & Fernandez-Rey, 2010). These individuals developed negative self but positive others model.…”
Section: Discussionmentioning
confidence: 99%